Bioscience will be the key that allows Africa to feed itself - International Livestock Research Institute (2010)
Biosciences offer the opportunity for many regions in Africa to produce surplus food for the first time. Without biosciences research within African agriculture will face a difficult future. The Bio-Innovate program is therefore important because it will stimulate new industries that are linked to the life sciences. Farmers will not benefit from producing more food unless they can get it to markets to process and sell. Calestous Juma is the Director of the Science, Technology and Globalization Project at the John F. Kennedy School of Government at Harvard University, USA.